(Re) Assessing the (in) Efficacy of Traditional Medicine among the NSO and Bakweri of Cameroon: Historical and Contemporary Perspectives (London Journal of Medical and Health Research, 2025)
Traditional Medicine (TM) which was pioneer in satisfying mans health needs posed as one of those cultural aspects of centrality to the social and political economies of most communities in Africa South of the Sahara. Conventional medicine has its roots in traditional healing practices, as many early medical discoveries were derived from traditional herbal knowledge. Otherwise, the base of conventional medicine was first laid by TM. The question of efficacy looms over TM as a serious debate ensues among scholars for example: in Cameroon, as to its effectiveness which have been sustained for more than a century. So, though TM among the Nso and Bakweri was widely known for its effectiveness in the nineteenth and twentieth centuries, it seems as though sparsely and at times administration of herbal treatment did not meet up to expectations as diseases it was intended to treat or heal persisted despite administration of herbal concoctions. Reasons account for this backdrop which are pinpointed and analysed herein. Inter-disciplinarity and content analysis form the methodological blocks of this manuscript, meanwhile primary and secondary sources will be used for data collection. The findings reveal that TM was effective but the activities of some practitioners had/has tempered with the efficacy of TM in one way or the other; deontological concerns/(in)adherence has its paw on the question as far as the efficacy/inefficacy of TM is concerned, the nature of certain illnesses, among others. Overtime, this practice has also evolved with significant improvement in packaging and hygienic conditions. The findings also revealed the fact that though TM failed to treat some illnesses does not demonstrate inefficacy, since individual traditional healers at times failed to respect the norms of treatment.
Keywords: urogenital abnormality; anorectal malformation; Creatinine; Electrolytes; Urea.; Biochemical parameters; dengue patients; serum albumin; serum ALT; Indigenous Knowledge; traditional medicine (tm); herbs; nso; bakweri; efficacy; inefficacy; traditional healers; herbal remedies; medical anthropology.